Common Interests, Uncommon Goals
XVIII, 386 p.
Keywords: The World Council of Comparative Education Societies (WCCES) was established in 1970 as an umbrella body which brought together five national and regional comparative education societies. Over the decades it greatly expanded, and now embraces three dozen societies. This book presents histories of the WCCES and its member societies. It shows ways in which the field has changed over the decades, and the forces which have shaped it in different parts of the world. The book demonstrates that while comparative education can be seen as a single global field, it has different characteristics in different countries and cultures. In this sense, the book presents a comparison of comparisons.